Metal Cellulose Nanocomposites in Decorative Animation Character Modeling - Lili Zhang (Advances in Materials Science and Engineering)
With the development of economy, people’s research on nanomaterials has become more and more, and nanomaterials can be applied in many fields, such as medicine and building materials. The animation character modeling is very important in the cartoon, and the decoration of the animation character modeling can help improve people’s interest in watching cartoons and improve the quality of cartoons. This paper aims to study the role of metal cellulose nanocomposites in the modeling of decorative animation characters. In this paper, the principles and basic concepts of metal cellulose nanocomposites are presented, as well as the analysis of their properties. The experimental results in this paper show that the adsorption of copper in cellulose nanocomposites reaches 256.28 mg/g, the adsorption of chromium is 40.73 mg/g, and the adsorption of cadmium is 47.20 mg/g. The adsorption of other materials to copper is only 80.44 mg/g, the adsorption of chromium (VI) is only 1.116 mg/g, and the adsorption of cadmium is only 9.487 mg/g. It can be seen that the adsorption capacity of cellulose nanocomposites is much higher than that of other materials, so the adsorption properties of cellulose nanocomposites are very strong and can be applied in many fields.